Automatic control technology of low frequency and low voltage splitting devices using wide area measurement information - Mingliang GAO; Bo ZHUANG; Xuefei NIU; Mouying LI (Dianxin kexue)
Aiming at the problems of large noise content of wide area measurement information of power grid and difficulty in controlling oscillation damping in interconnected areas of power grid, an automatic control technology of low frequency and low voltage splitting devices using wide area measurement information was proposed.Based on the wide area measurement system (WAMS), the wide area measurement information of the power grid during the operation was obtained.After the noise contained in the wide area measurement information of the power grid was removed by the wavelet decomposition de-noising method, the power grid low-frequency oscillation identification method based on Prony was used to identify the power grid oscillation region and oscillation value.Then, based on the grid oscillation region and oscillation value, the oscillation center voltage and positioning coefficient were calculated and used as input to design the automatic control flow of the low frequency and low voltage splitting device, so as to realize the automatic control of the low frequency and low voltage splitting device.The experimental results show that this method can effectively remove the noise contained in the wide area measurement information of the power grid, the maximum error of the oscillation damping value in the interconnected area of the power grid is only 0.01, and this method can effectively control the low frequency and low voltage splitting device.